2009
DOI: 10.1063/1.3116728
|View full text |Cite
|
Sign up to set email alerts
|

Reducing current loss of laser-driven fast electron beams propagating in solid-density plasmas

Abstract: A scheme to reduce the current loss of laser-driven energetic electron beams propagating in solid-density targets is proposed. In the scheme, two intense laser pulses irradiate the solid target consisting of two materials, one enveloping the other. Because of the resistivity and density gradients at the material interface, the first pulse generates tens of megagauss robust interface magnetic fields that can considerably reduce the divergence of the electron beam generated by the second pulse. It is shown that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…In standard PIC simulation (Birdsall & Langdon, 1985), the size of each cell has to be smaller than the Debye length in order to avoid numerical instability. Recently, numerical techniques based on hybrid simulations have been extensively applied for the study of beam-plasma interactions (Welch et al, 2001;Davies, 2003;Honrubia et al, 2005;Campbell et al, 2005;Evans, 2006;Solodov et al, 2009;Zhou et al, 2009). In this work, we shall not consider the initial laser-cone interaction, which has been investigated by many authors (Gibbon, 2005;Cai et al, 2009;Wu et al, 2010).…”
Section: Physical Description and Simulationmentioning
confidence: 97%
“…In standard PIC simulation (Birdsall & Langdon, 1985), the size of each cell has to be smaller than the Debye length in order to avoid numerical instability. Recently, numerical techniques based on hybrid simulations have been extensively applied for the study of beam-plasma interactions (Welch et al, 2001;Davies, 2003;Honrubia et al, 2005;Campbell et al, 2005;Evans, 2006;Solodov et al, 2009;Zhou et al, 2009). In this work, we shall not consider the initial laser-cone interaction, which has been investigated by many authors (Gibbon, 2005;Cai et al, 2009;Wu et al, 2010).…”
Section: Physical Description and Simulationmentioning
confidence: 97%
“…2 It usually relies on enhancement in the collimating magnetic field by properly tailoring the profiles of the laser pulse and/or the target. 10,[14][15][16][17][18] Recently, several schemes for reducing the lateral divergence of laser produced electron beams have been proposed based on the hybrid simulation results, such as the Vlasov-Fokker-Planck ͑VFP͒ simulation, 10,15 the hybrid fluid-particle-in-cell ͑HFPIC͒ simulation, 14,17 etc. The most recent experiments have shown that a structured target can indeed improve electron beam concentration.…”
Section: Effect Of Density Profile On Beam Control Of Intense Laser-gmentioning
confidence: 99%
“…This is also the physical mechanism that the previously proposed magnetic collimation schemes considered. 14,15,17 They mainly put emphasis on the normal collisional resistivity effect while neglecting the effect of the plasma density and the related anomalous resistivity, which is the main subject of this paper.…”
Section: Physical Model and Simulationmentioning
confidence: 99%